The Role of Sharia Audit in Detecting Fraud in Islamic Financial Institutions - Putri, Anggi Amalia; Purba, Ance; Nisa, Asy Syifa Qudwatun; Setiyawati, Agustin (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to examine the effect of sharia compliance, sharia audit, Good Corporate Governance (GCG), and internal control on fraud in Islamic financial institutions in Indonesia. The research employs a quantitative approach with an associative method, using secondary data obtained from financial statements, annual reports, and GCG reports of Islamic commercial banks. The sampling technique used is purposive sampling, and data are analyzed using multiple linear regression. The results indicate that sharia compliance, sharia audit, GCG, and internal control play significant roles in reducing fraud. Sharia compliance enhances transparency and accountability, sharia audit functions as a monitoring and early detection mechanism, GCG strengthens corporate governance, and internal control reduces opportunities for fraud. Simultaneously, these variables contribute to minimizing fraud risk.